DASAR PENDIDIKAN ANAK USIA DINI MENUJU PENDIDIKAN SEKOLAH DASAR - Rr Dina Kusuma Wardhani (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2022)
Early childhood education (0-8 years) is a golden age as an effort to provide stimulation, guide, nurture in learning activities so as to produce abilities and skills in these children. The educational environment given to children must support children's development, so that children are able to explore their abilities through seeing, imitating and experimenting and there is a process of maturity of physical and psychological functions in children, children are ready to respond to their environment and carry out daily developmental tasks according to their age. The purpose of this research is as an effort to provide an understanding of Early Childhood Education which will certainly experience changes towards elementary school. The method used is in the form of data collection techniques through literature searches and journal reviews. The results of the study are in the form of a golden age for children where at this time the development and growth of children is very fast, and at this time it is considered a very appropriate time to explore all the potential that is owned in children such as various aspects of child development. By knowing the characteristics of class students in elementary schools, the teacher or educator can plan learning according to the development and characteristics of these students. Thematic learning allows students to understand something from all sides. In turn, this will make students wiser and wiser in dealing with the events they will encounter.